Tecnologias móveis na educação: estudo em duas experiências na educação a distância - Domenciano, Jaqueline Ferreira (2015)
Mobile learning refers to learning processes supported by the use of mobile and wireless technologies, in the process of teaching and learning. This research aims at studying the literature and the use experiences of mobile technologies, such as mobile phones and tablets, in education, by observing the adopted materials and methods, and the results obtained. After a literature review, an exploratory study was conducted through interviews with course coordinators and questionnaires with students and teachers in order to identify which resources of mobile technologies have been used in virtual graduate courses and with which academic purpose. The results show a major concern of the universities analyzed for the adaptation of their teaching materials and the development of specific tools for mobile learning. The study showed that most students and teachers of this study is making an adapted use of the mobile communication technologies. This use involves the access to teaching material (reading, video, audio), the interactive environments (student/student, student/teacher, teacher/teacher), the school calendar and even file sharing from mobile devices. Of the four courses analyzed, only one is making systematic use of mobile devices, which is the course of Musical Education, from the Federal University of São Carlos, which has 25 subjects (54% of the offered courses) with teaching materials developed specifically for use on mobile devices, through the ePub. The results obtained in this study may be useful to the institutions analyzed and other interested, by supporting the development or improvement of pedagogical practices involving mobile communication devices.